Effects of Mannan Oligosaccharides and/or Bifidobacterium on Growth and Immunity in Domestic Pigeon (Columba livia domestica) - Bingjie Ge; Haiming Yang; Jun Meng; Xiaoshuai Chen; Zhiyue Wang (The Journal of Poultry Science, 2020)
The goal of this study was to evaluate the influences of mannan oligosaccharides (MOSs) and/or Bifidobacterium on the growth and immunity of pigeons over a 56-day period. One hundred paired adult pigeons were randomly divided into four groups of five paired pigeons. Paired pigeons with two young squabs were housed in a man-made aviary. Parent pigeons in the control group received a basal diet (C), while the other three groups were fed with the basal diet supplemented with 20 g of MOSs/kg of feed (M), 10 g Bifidobacterium (1×1010 CFU/g)/kg of feed (B), or a combination of M and B (MB). We found higher body weights (BW) in pigeons of the B group than in the C, M, and MB groups. None of the treatments exerted significant effects involving spleen and thymus indices, whereas M birds tended to improve the bursa of Fabricius index. Pigeons fed with the M-supplemented diet exhibited improved serum immunoglobulin M (IgM) concentrations compared with those fed with C and the B- and MB-supplemented diets. In addition, M treatment increased immunoglobulin A (IgA) levels compared with MB treatment. MB treatment improved serum immunoglobulin G (IgG) concentrations compared to that by the C treatment. The concentration of secretory immunoglobulin A (sIgA) was significantly reduced in the duodenum and increased in the ileum in pigeons fed with the MB-supplemented diet. This study indicated that dietary supplementation with Bifidobacterium increased the growth performance. Dietary supplementation with MOSs or in combination with Bifidobacterium was able to improve immune function in pigeons but exerted no apparent effect on weight gain. Accordingly, in terms of economic benefits, the findings suggested that supplementation with Bifidobacterium alone may improve production performance, and that supplementation with MOSs alone may improve immune function in pigeons.